Mapping of the research, innovation and diffusion activity of CRISPR across countries - Samantha Zyontz; Cassidy Pomeroy-Carter (Expertenkommission Forschung und Innovation (EFI), 2021)
CRISPR, a breakthrough technology that can modify or screen DNA in almost any organism, has profoundly influenced innovation in a range of applications. Recognizing the importance of CRISPR, the 2020 Nobel Prize winning technology, the EFI commissioned this project to map the research, innovation, and diffusion activity of CRISPR across countries. This report provides four new databases that capture the population of publicly available information on CRISPR academic articles, patent families, companies, and clinical trials geographically, temporally, and across application areas. The data show that Germany actively participates in the CRISPR ecosystem but countries appear to focus on different niche areas consistent with their existing academic, business, and cultural environments at the time CRISPR was introduced. These results suggest several implications for German CRISPR innovation strategies. E.g. Germany is well positioned for a niche strategy of creating quality solutions for the biggest CRISPR challenges. Further could the support for German academic and corporate partnerships encourage translation from labs to commercialization.
Keywords: 330